Exploration of C5–C6-Unsubstituted 1,4-Dihydropyridines for the Construction of exo-Hexahydro-1H-chromeno[3,4-h][1,6]naphthyridine-3-carboxylates Using a Stereoselective Povarov Reaction - Islam, Kobirul; Das, Deb K.; Akram, Ejaz; Khan, Abu T. (Synthesis, 2015)
A wide variety of substituted exo-hexahydro-1H-chromeno[3,4-h][1,6]naphthyridine-3-carboxylate derivatives have been synthesized from 3-aminocoumarins, aldehydes, and 5,6-unsubstituted 1,4-dihydropyridine derivatives in the presence of 10 mol% of ytterbium(III) triflate in acetonitrile at room temperature using a one-pot Povarov reaction. Some of the salient features of this protocol are: good yields and no need for an aqueous workup procedure or chromatographic separation.
Keywords: aromatic aldehydes; 1,4-dihydropyridines; 3-aminocoumarin; Povarov reaction; ytterbium(III) triflate